Peningkatan Kualitas Sumber Daya Manusia Digital Pondok Pesantren (Studi Kasus di Pondok Pesantren Bidayatul Hidayah Mojogeneng Jatirejo Mojokerto) - Isno isno (PROGRESSA: Journal of Islamic Religious Instruction, 2017)
Human resources have a central position in realizing development performance. "The era of globalization today and in the future coupled with information technology has influenced the socio-cultural development of Indonesian Muslim society generally, or Islamic education, including pesantren in particular". That the Muslim community can not escape from the process of globalization, especially if you want to survive and triumph in the midst of an increasingly competitive world in the present and future. Based on the background, this study aims to examine the Improvement of the Quality of Digital Human Resources in Pondok Pesantren Bidayatul Hidayah Mojogeneng Jatirejo Mojokerto. This research is descriptive qualitative research. The researcher acts as a data collector and as an active instrument in the effort to collect data in the field. To obtain data related to the theme of research, used some data collection techniques as follows: Observation or observation Interview, and Documentation. Data analysis of the results of this study, conducted based on descriptive analysis, as developed by Mile and Huberman. The analysis consists of three interaction analysis paths that are data reduction, data presentation and conclusion drawing. From the results of the discussion can be concluded that Pondok Pesantren Bidayatul Hidayah Mojogeneng Jatirejo Mojokerto in order to Improve the Quality of Digital Human Resources do things as follows: 1) Development and Mastery Book Yellow / Salaf. 2) Program of development of basic sciences. Many benefits are felt with this program, including: a. The level of readiness of students to receive lessons is better. b. Ability of students to absorb material faster. c. Student creativity and motivation increase. 3) Development of Foreign Language Ability. 4) Development of Pesantren Through the Utilization of Information and Telecommunication Technology (ICT). 5) Improvement of the role of Organization of Santri / Santriwati. 6) Increasing Pesantren's Contribution to Community Development